Study of Vibrating Screen Machine Damage in Stone Crusher and Its Effect on Production Loss in Cement Factory - Kaspul Anuar; Herisiswanto Herisiswanto; Aqsal Fahrizqa (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2023)
Vibrating Screen Machine have a crucial role in producing split stone. Vibrating screen machine maintenance is taken after it is in trouble. This is a kind of unplanned maintenance, which risks causing a high quantity of machine breakdowns and will affect to the production capacity. This study analyses data trouble of the vibrating screen machine for five months. The data analysed are the type of disturbance, the amount of production losses and financial losses. The results showed that the largest repair hours due to mechanical problem occurred in the fifth month with a repair time of 75.8 hours and a production loss of 5,269.85 Tons which is equivalent to Rp. 580,382,000,-. Then the largest total repair hours due to the production problem occurred in the second month with a repair time of 32.99 hours and a production loss of 968.49 Tons or equivalent to Rp. 179,385,000,-. Salah satu jenis mesin yang beperan dalam memproduksi batu split adalah vibrating screen. Perawatan mesin vibrating screen biasanya dilakukan saat mesin mengalami kerusakan. Hal ini adalah bentuk pemeliharaan yang tidak terencana, yang beresiko menimbulkan tingginya kuantitas gangguan pada mesin dan akan mempengaruhi kapasitas produksi. Penelitian ini menganalisa data gangguan dari mesin vibrating screen selama lima bulan. Data yang dianalisis meliputi tipe gangguan, jumlah produksi yang hilang (production losses) dan rugi keuangan. Hasil penelitian menunjukkan total jam perbaikan dengan klasifikasi kerusakan mechanical terbesar terjadi pada bulan ke lima dengan waktu perbaikan selama 75,8 jam dan production loss sebesar 5.269,85 Ton yang setara dengan Rp. 580.382.000,-. Kemudian total jam perbaikan dengan klasifikasi kerusakan production terbesar terjadi pada bulan kedua dengan waktu perbaikan 32,99 jam dan kerugian hasil produksi sebesar 968,49 Ton atau setara dengan sebesar Rp. 179.385.000,-.